ANALISA KESELAMATAN DAN KESEHATAN KERJA PADA PEMBANGUNAN PROYEK SILKTOWN ALEXANDRIA TOWER APARTEMEN - Nawa, Syayid; Rijaluddin, Arief (Universitas Majalengka, 2019)
Occupational Health and Safety (K3) is a program created by both work and employers as an effort to prevent work-related accidents and illnesses as well as anticipatory action in the event of work-related accidents and illnesses. The goal is to create a safe, healthy workplace so that it can reduce the risk of accidents and illness as low as possible. The level of occupational safety and health (K3) in PT Nusa Raya Cipta (NRC) is still often overlooked. This is indicated by the high number of work accidents that occur at PT Nusa Raya Cipta, this situation has an impact on the decline in company performance. Knowing the K3 implementation system in the field in accordance with the SMK3 in the field includes planning, operational and realization. Knowing the OSH system in the field where starting from safety talk is done every Friday before work begins, safety patrol is a routine patrol conducted by the safety team to monitor and supervise all OHS construction and inspection activities to check and ensure that contractors and subcontractors and foremen carry out OHS. The research results of the alexsandri silk town apartment development project is one of the construction projects that has a high risk of work accidents. One reason is the use of heavy equipment and sophisticated machinery that requires expertise to use it properly. Therefore it is necessary to conduct research on the evaluation of the application of SMK3 to the project so that work accidents can be reduced or reduced to a minimum. Work safety and health management that is carried out as well as possible is expected to provide a climate of security and calm work, so it is very helpful in increasing labor productivity.